1989
DOI: 10.1021/bi00452a002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of complement factor H mRNA expression: dexamethasone and IFN-.gamma. increase the level of H in L cells

Abstract: Murine complement protein H is encoded by a 100-kb gene on chromosome 1. A 3.2-kb fragment of the 5' flanking region of the H gene was sequenced, and two transcription start sites for this gene were identified by RNase protection and S1 nuclease analyses, each of which had upstream TATA and CAAT boxes. This region shares sequence homology with known regulatory elements, including the SV40 enhancer consensus, the Sp1 binding site, and two glucocorticoid-responsive core elements (GRE). Tissue and cell-line speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 36 publications
3
11
0
Order By: Relevance
“…Although it had not been shown before in these cell types, the IFN-␥-mediated up-regulation that was observed here for HC and KC was not unexpected because this phenomenon had formerly been observed in HUVEC (Brooimans et al, 1989;Dauchel at al, 1990;Lappin et al, 1992;Ripoche et al, 1988b;Schlaf et al, 2001), in primary myoblasts and in two rhabdomyosarcoma cell lines (CRL 1558 and HTB 153) (Legoedec et al, 1995), in primary fibroblasts (Friese et al, 1999;Katz and Strunk, 1988;Lappin et al, 1992;Schwaeble et al, 1991), in fibroblast-like L cells (Munoz-Canoves et al, 1989), in monocytes (Lappin et al, 1992), in the murine liver cell line ϩ/ϩLi (Vik, 1996), and in the human Hep3b hepatoma cell line (Luo and Vik, 1999) and may therefore be a common feature. In the present study, the proinflammatory cytokines TNF-␣, IL-6, and IL-1␤ did not upregulate FH.…”
Section: Factor H In Primary Liversupporting
confidence: 63%
See 1 more Smart Citation
“…Although it had not been shown before in these cell types, the IFN-␥-mediated up-regulation that was observed here for HC and KC was not unexpected because this phenomenon had formerly been observed in HUVEC (Brooimans et al, 1989;Dauchel at al, 1990;Lappin et al, 1992;Ripoche et al, 1988b;Schlaf et al, 2001), in primary myoblasts and in two rhabdomyosarcoma cell lines (CRL 1558 and HTB 153) (Legoedec et al, 1995), in primary fibroblasts (Friese et al, 1999;Katz and Strunk, 1988;Lappin et al, 1992;Schwaeble et al, 1991), in fibroblast-like L cells (Munoz-Canoves et al, 1989), in monocytes (Lappin et al, 1992), in the murine liver cell line ϩ/ϩLi (Vik, 1996), and in the human Hep3b hepatoma cell line (Luo and Vik, 1999) and may therefore be a common feature. In the present study, the proinflammatory cytokines TNF-␣, IL-6, and IL-1␤ did not upregulate FH.…”
Section: Factor H In Primary Liversupporting
confidence: 63%
“…The primary site of synthesis of FH is the liver (Zipfel and Skerka, 1994). Extrahepatic cell types such as human umbilical vein endothelial cells (HUVEC) (Brooimans et al, 1989(Brooimans et al, , 1990Ripoche et al, 1988b), peripheral blood monocytes (Whaley, 1980), cells of the monocytemacrophage series (De Ceulaer et al, 1980), primary skin fibroblasts (Katz and Strunk, 1988), fibroblast-like L cells (Munoz-Canoves et al, 1989;Vik, 1999), primary myoblasts and rhabdomyosarcoma cell lines (Legoedec et al, 1995), glioma cell lines (Gasque et al, 1992), and glomerular mesangial cells (van den Dobbelsteen et al, 1994) have also been reported to express FH. These cell types may function as local sources of FH and thereby reduce tissue damage caused by local complement activation.…”
mentioning
confidence: 99%
“…fH, however, is also synthesized de novo at various sites in the body, including the lung (6), skin fibroblasts (16), kidney (23,29), spleen (23), thymus (23), endothelial cells (25), and synovial fluid (11), and by primary human cervical epithelial cells (8). The newly developed human fH transgenic rat model expresses fH from a chicken betaactin promoter, which could result in expression of this protein at sites that do not normally express fH.…”
Section: Figmentioning
confidence: 99%
“…These results suggest that analogous to the findings with C3 allotypes, screening for MCP, fH, and fI polymorphisms could ultimately direct management and improve patient outcome. Moreover, combined liver-kidney transplantation in appropriate cases offers a means to replace the defective fH, which is mainly produced by hepatic synthesis [37,38]. This has been the subject of recent review [39].…”
Section: Genetic Polymorphisms In Complement Proteins/regulators and mentioning
confidence: 99%